Kehujjahan Urf dalam Hukum Islam - Muhammad Rif`an Ilham (Jurnal Teologi Islam, 2026)
This study discusses the position and validity of ‘urf as one of the legal foundations in Islamic law. ‘Urf is a habit or tradition that develops continuously within society and is recognized as something good by reason and social norms. The purpose of this study is to explain the meaning of ‘urf, its types, and its role as a legal argument in determining Islamic law. The method used in this research is a literature study by collecting data from books, scientific journals, and related articles. The results show that ‘urf can be used as a legal basis as long as it does not contradict the Qur’an, hadith, and the principles of Islamic law. Islamic scholars from various schools of thought acknowledge the existence of ‘urf shahih as a valid legal consideration, especially in matters not explicitly regulated in the religious texts. The existence of ‘urf demonstrates that Islamic law is flexible and capable of adapting to social and cultural developments in society. Therefore, ‘urf has an important role in maintaining public benefit and making Islamic law relevant in different times and places.